Quantitative Nature of Social Vulnerability and Autism: An Important Paradigm Shift in the DSM-5 for Autism Spectrum Disorder. (8th May 2013) - Ijichi, Shinji; Ijichi, Naomi; Ijichi, Yukina; Hirotaki, Kazumi; Sameshima, Hisami; Kawaike, Yoichi; Morioka, Hirofumi
Abstract : In the Diagnostic and Statistical Manual of Mental Disorders, 4th edition (DSM-IV), autistic characteristics in social interaction and communication are described as qualitative impairments. However, the difference between autistics and nonautistics in the draft of the 5th edition (DSM-5 draft) is quantitative rather than qualitative. The word "qualitative" is deleted in the draft text, and it is specified that the relation between social demands and individual limited capacities is critical for symptom manifestation (criterion C). Because the proposed levels of support requirement in the draft are mere observable outcomes of social vulnerability, the boundary between level 1 and nonautistic condition is determined by the relation between social demands and individual capacities. In addition to the introduction of the single category (autism spectrum disorder (ASD)) to cover the entire case spectrum, the DSM-5 draft is clearly based on a conviction that ASD is indistinguishable from the normal behavioral range. This concise review provides an explanation for this implicit paradigm shift from qualitative to quantitative. Importantly, the conditional role of social demands for symptom manifestation in the draft can be plausibly interpreted using a unique liability-probability model.